The S100 calcium binding protein A11 promotes liver fibrogenesis by targeting TGF-β signaling. (April 2022) - Zhu, Tingting; Zhang, Linqiang; Li, Chengbin; Tan, Xiaoqiong; Liu, Jing; Huiqin Li,; Fan, Qijing; Zhang, Zhiguo; Zhan, Mingfeng; Fu, Lin; Luo, Jinbo; Geng, Jiawei; et al.
Abstract: Liver fibrosis is a key transformation stage and also a reversible pathological process in various types of chronic liver diseases. However, the pathogenesis of liver fibrosis still remains elusive. Here, we report that the calcium binding protein A11 (S100A11) is consistently upregulated in the integrated data from GSE liver fibrosis and tree shrew liver proteomics. S100A11 is also experimentally activated in liver fibrosis in mouse, rat, tree shrew, and human with liver fibrosis. While overexpression of S100A11 in vivo and in vitro exacerbates liver fibrosis, the inhibition of S100A11 improves liver fibrosis. Mechanistically, S100A11 activates hepatic stellate cells (HSCs) and the fibrogenesis process via the regulation of the deacetylation of Smad3 in the TGF-β signaling pathway. S100A11 physically interacts with SIRT6, a deacetylase of Smad2/3, which may competitively inhibit the interaction between SIRT6 and Smad2/3. The subsequent release and activation of Smad2/3 promote the activation of HSCs and fibrogenesis. Additionally, a significant elevation of S100A11 in serum is observed in clinical patients. Our study uncovers S100A11 as a novel profibrogenic factor in liver fibrosis, which may represent both a potential biomarker and a promising therapy target for treating liver fibrosis and fibrosis-related liver diseases.